CGIAR Research Program on Maize - Plan of Work and Budget 2020 - CGIAR Research Program on Maize (CGIAR Research Program on Maize, 2020)
No new adjustments planned, however adjustments initiated in 2019 will continue in 2020: • FP3: Continue to update Theory of Change and Impact Pathway (ToC & IP) by adding a consumer/demand-foresight component to MAIZE breeding product profiles. By 2021, MAIZE aims to expand its research scope, in terms of feed and fodder traits and will investigate new partnerships in Southeast Asia. • FP4: Due to departure of two key IRS in early 2020 in charge of CoA 4.2, leadership of that cluster and synthesis work is sub-granted to Wageningen University (WUR). The FP4 project portfolio is evolving, with greater emphasis on environmental issues (e.g. crop residue burning, water scarcity in South Asia). • All FPs: W1/2 MAIZE funds will be strategically invested in co-shaping the future CGIAR research portfolio, which would in turn impact MAIZE 2022+ Theories of Change. Examples of MAIZE participation in new initiative design ongoing in 2020 are: Excellence in Agronomy, DryArc and the 2Degrees Initiative.